ANALISIS YURIDIS TERHADAP PUTUSAN HAKIM YANG TERDAKWANYA TIDAK DIDAMPINGI PENASIHAT HUKUM - Rakhbir Singh; Dian Adriawan Daeng Tawang (Reformasi Hukum Trisakti, 2022)
The Baturaja District Court's ruling, Judge Number: 7/PID.B/2019/PN.BTA, does not offer the attempted murder defendant any pre-trial legal counsel or legal remedies. Normative justice is the study methodology used, and the research's primary objective is based on constructive legal standards or norms. The type of descriptive analytical research. This denotes a thorough, in-depth, and methodical analysis. The request from the prosecutor was rejected. The Attorney General's Office's allegations are ruled untrue, and the judgment is regarded as having never been reached. According to Article 56 (1) of the Criminal Code, judges in murder trials have a duty to counsel defendants. The accused may file an appeal with the Advocate Honorary Council.